The wider costs and benefits of urban public transport systems - Brand, C; Preston, J (Transport Studies Unit, University of Oxford, 2002)
This review of the costs and benefits associated with public transport includes: the benefits to users over and above those captured by the fare box, including time savings and reliability improvements; the benefits to non-users as a result of reduced congestion and reduced accidents; an assessment of the environmental impacts, including local and global air emissions and visual intrusion; and an assessment of the impacts on land use, accessibility and integration. Public transport systems covered include urban rail, urban bus, light rail, underground railways, bus lanes, busways, guided buses and personal public transport in the UK. For buses air pollution costs are higher than noise and global warming costs. Noise pollution is more significant for rail-based systems. Air pollution costs are higher in urban areas. Diesel trains in urban locations show relatively high pollution costs. Light rail and bus accident costs are considered to be similar. Bus-based and suburban rail systems had the lowest operating cost, closely followed by light rail. Underground railways cost three times as much to run on the same basis. Public transport modes with higher operational speeds and off-vehcile fare collection showed journey time advantages over some of the slower modes (buses and light rail in mixed traffic). While underground systems had the lowest community severance problems, they had low scores on accessibility for disabled people. Technology that may be easily integrated into existing transport systems showed high public acceptability. A framework for social costing is presented.